The efficacy of voice therapy for Bangladeshi patients with vocal fold nodules (Dhaka University Journal of Biological Sciences, 2024)
Voice therapy in improving the voice quality of vocal fold nodule patientshas evidentiary support. This study aimed to investigate the efficacy of voicetherapy for Bangladeshi patients (N=30) with vocal fold nodules, as well as thefactors (therapy practice and maintenance of vocal hygiene) that influence theeffectiveness or outcome of voice therapy in treating vocal fold nodules. This studywas an observational cohort study of 30 Bangladeshi adult patients with vocalfold nodules (mean age=41; SD= 8.78). Before and after voice therapy, Phonationexercises and narrative-telling tasks were used to elicit voice features, and the sizeof vocal fold nodules was observed through Fiber Optic Laryngoscopy (FOL). Thedata was statistically analyzed using the percentage/proportion test and Fisher’sexact test to demonstrate the success of voice therapy and the factors impactingthe therapy’s efficacy. The findings indicated that voice therapy was successfulfor most participants (87%). Practicing therapy regularly and maintaining vocalhygiene had an impact on therapy success.